Mechanics of Fatigue Crack Closure 1988
DOI: 10.1520/stp27217s
|View full text |Cite
|
Sign up to set email alerts
|

Development of Fatigue Crack Closure with the Extension of Long and Short Cracks in Aluminum Alloy 2124: A Comparison of Experimental and Numerical Results

Abstract: The development of crack closure during the extension of long and short fatigue cracks has been investigated in a 2124 aluminum alloy using both experimental and numerical procedures. Specifically, the growth rate and closure behavior of long (∼17 to 38 mm) cracks in compact C(T) specimens and through-thickness physically-short (∼50 to 40 μm) cracks in single-edge-notched SEN(B) bend specimens have been examined experimentally from threshold levels to instability (over the range ∼10−12 to 10−7 m/cycle), and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…This is in agreement with the conclusion obtained for through thickness cracks by Ritchie et al [40], who found that for a coarse-grain 2124 aluminium alloy the magnitude of fatigue crack closure measured experimentally for both long and short cracks was consistently higher than that obtained from an elastic-plastic finite element analysis under plane strain conditions. In addition, it can be seen from Eq.…”
Section: A Simple Model For Fatigue Crack Closuresupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with the conclusion obtained for through thickness cracks by Ritchie et al [40], who found that for a coarse-grain 2124 aluminium alloy the magnitude of fatigue crack closure measured experimentally for both long and short cracks was consistently higher than that obtained from an elastic-plastic finite element analysis under plane strain conditions. In addition, it can be seen from Eq.…”
Section: A Simple Model For Fatigue Crack Closuresupporting
confidence: 93%
“…If the stress level at which the COD on the specimen surface (@ = 0) is reduced to zero is defined as the closure stress, the above results indicate that the plasticity-induced fatigue crack closure stress on the specimen surface for three dimensional semi-circular cracks does not change with a change of fatigue crack length. For through thickness cracks, the independence of crack closure stress on crack length for plasticity-induced closure has been suggested by several previous studies [20,21,24,40]. One interesting indication from Figs 4(a) and 4(b) is that on reaching a fixed COD (non-zero), the smaller the crack is then the higher is the applied stress.…”
supporting
confidence: 62%
“… Schematic representation of typical behaviours of small cracks under CA loading in smooth and notched specimens 122 …”
Section: Crack Closure In Plane Strain Conditionsmentioning
confidence: 99%
“…Many investigators have suggested that crack closure can be a major factor in causing some of the differences between the growth of long and short cracks 94 , 109 , 121 –124 . A crack freshly initiated from a microstructural defect or in an intense slip region has no previous fatigue history and therefore no wake of plastic deformation.…”
Section: Crack Closure In Plane Strain Conditionsmentioning
confidence: 99%
“…Anomalous crack growth at notches (Figure 7) is often illustrated below the long crack threshold (e.g. Ritchie et al 1988, Janssen et al 2002 and suggested to be a result of missing crack growth driving force (correction) components like K t or Y n . Plasticity induced crack closure, i.e.…”
Section: Crack Tip Stress Intensity Criterionmentioning
confidence: 99%